2018
DOI: 10.1111/jgs.15492
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis of Chikungunya Virus Infection: Comparison of Old and Younger Adults

Abstract: Misdiagnosis of CVI during an epidemic is statistically more frequent in older than younger adults because clinical presentation is often atypical in older adults. Specific diagnostic tools for older adults and better awareness of ED physicians of different presentations in different age groups could help to reduce the rate of misdiagnosis of CVI in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The rate of lost to follow-up was high, though phone calls helped to reduce it. Second, the study cohort did not fully reflect the population affected by the epidemic because subjects were not sampled from the general population; thus, data for elders may be missing as their symptoms are atypical and easily misdiagnosed [87,88]. Third, the plasma viral load of CCA and no CCA patients could not be measured due to a lack of funding; however, future studies could exploit our biological bank to assess this variable and to conduct other immunological and virological investigations.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The rate of lost to follow-up was high, though phone calls helped to reduce it. Second, the study cohort did not fully reflect the population affected by the epidemic because subjects were not sampled from the general population; thus, data for elders may be missing as their symptoms are atypical and easily misdiagnosed [87,88]. Third, the plasma viral load of CCA and no CCA patients could not be measured due to a lack of funding; however, future studies could exploit our biological bank to assess this variable and to conduct other immunological and virological investigations.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…It has been observed that young children present with arthralgia less frequently than older children and adults (52,54,57,72). Patients older than 65 years of age may present a more complicated clinical picture during acute chikungunya, with more frequent manifestations other than arthralgia, including high rates of neurological complaints (73). Limited data are available from immunocompromised hosts, but chikungunya manifestations and severity do not appear to differ among solid organ transplant recipients (74).…”
Section: Acute Clinical Presentation and Differential Diagnosismentioning
confidence: 99%
“…In the context of CVI, Godaert et al . showed that diagnostic errors were more frequent in elderly subjects than in their younger counterparts. The authors hypothesised that the atypical presentation of CVI in this population contributes to diagnostic uncertainty, and may induce a delay in management that could be prejudicial for the patient.…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of intercurrent signs during CVI can complicate the patient's clinical course and/or reveal latent disease that had not previously been diagnosed. In the context of CVI, Godaert et al [30] showed that diagnostic errors were more frequent in elderly subjects than in their younger counterparts. The authors hypothesised that the atypical presentation of CVI in this population contributes to diagnostic uncertainty, and may induce a delay in management that could be prejudicial for the patient.…”
Section: Discussionmentioning
confidence: 99%